Control of Quaternary sea‐level changes on gas seeps. Issue 14 (29th July 2014) - Riboulot, Vincent; Thomas, Yannick; Berné, Serge; Jouet, Gwénaël; Cattaneo, Antonio
Abstract Gas seeping to the seafloor through structures such as pockmarks may contribute significantly to the enrichment of atmospheric greenhouse gases and global warming. Gas seeps in the Gulf of Lions, Western Mediterranean, are cyclical, and pockmark "life" is governed both by sediment accumulation on the continental margin and Quaternary climate changes. Three‐dimensional seismic data, correlated to multi‐proxy analysis of a deep borehole, have shown that these pockmarks are associated with oblique chimneys. The prograding chimney geometry demonstrates the syn‐sedimentary and long‐lasting functioning of the gas seeps. Gas chimneys have reworked chronologically constrained stratigraphic units and have functioned episodically, with maximum activity around sea level lowstands. Therefore, we argue that one of the main driving mechanisms responsible for their formation is the variation in hydrostatic pressure driven by relative sea level changes.